Research on Vibration Characteristics of Two-Speed Automatic Transmission Housing for Pure Electric Vehicles - Wang Yi; Chen Yong; Dai Qinglin; Zhang Haonan; Wu Yimin; Tian Naili; He Bolin (Jixie chuandong)
The research object is a two-speed double clutch automatic transmission (2DCT) of pure electric vehicles. Firstly, the modal simulation and test of the transmission housing are carried out to verify the accuracy of the finite element model of the housing. Then, considering the working efficiency of the motor, through the established dynamic model of the transmission system, the variation law of the transmission error of the gear pair under different torque conditions is obtained. The dynamic force of the bearing is further analyzed and taken as the boundary condition to study the vibration characteristics of the housing. By analyzing the modal participation factor (MPF), the modal order which contributes greatly to the shell vibration is determined. Finally, the vibration acceleration simulation and test of the obvious vibration area under multiple working conditions not only verify the accuracy of the dynamic model, but also further clarify the vibration characteristics of the 2DCT housing.